2009
DOI: 10.1136/oem.2008.039834
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone base stations and adverse health effects: phase 2 of a cross-sectional study with measured radio frequency electromagnetic fields

Abstract: In this large population-based study, measured RF-EMFs emitted from mobile phone base stations were not associated with adverse health effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
3
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 20 publications
6
64
3
4
Order By: Relevance
“…Therefore, it is reasonable to expect that the mechanism of biological activity of EMF emitted by transmitting antennas of base stations and mobile TV transmitters may be similar. This could explain subjective symptoms from the central nervous system (such as headache and dizziness) reported by the residents of areas surrounding base stations, observed by different authors [23,24,[31][32][33][34][35][36][37] where EMF with similar values prevail.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it is reasonable to expect that the mechanism of biological activity of EMF emitted by transmitting antennas of base stations and mobile TV transmitters may be similar. This could explain subjective symptoms from the central nervous system (such as headache and dizziness) reported by the residents of areas surrounding base stations, observed by different authors [23,24,[31][32][33][34][35][36][37] where EMF with similar values prevail.…”
Section: Discussionmentioning
confidence: 95%
“…Surveys using conventional psychological tests or questions with “yes” or “no” answers have been the most commonly used measures for the evaluation of effects of EMFs on health [Abdel‐Rassoul et al, 2007, Berg‐Beckhoff et al, 2009; Blettner et al, 2009]. However, investigations using conventional questionnaires failed to reveal any specific symptoms of EHS, nor clarified the severity of symptoms associated with exposure to specific EMF objects.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies 18 have failed to identify negative health effects in populations exposed to non-ionizing electromagnetic radiation. Blettner et al 19 found no association between living close to mobile phone base station and in-Cad.…”
Section: Introductionmentioning
confidence: 99%